Addition To Green-Based Feed Preparations With Fermentation Technology Innovation Good Ruminant Feeding Practices - Priyadi, Sapto; Fatchul Aziez, Achmad; Haryuni (Universitas Tunas Pembangunan Surakarta, 2024)
Improving ruminant feed quality is an important factor in increasing livestock productivity and health. To improve feed quality, accompanying forage-based ruminant feed preparation with fermentation technology innovation is the focus of community service activities. Accompanying forage-based ruminant feed preparations with a fermentation technology approach is intended to optimize the nutrition and microbial content in the feed, thereby increasing the availability of nutrients and digestion of livestock, with impact factors on growth, animal health, and milk production. Fermentation technology innovations can improve feed quality by increasing nutritional content, reducing anti-nutritional ingredients, and increasing nutritional availability for livestock without depending on or being influenced by changes from the rainy season to the dry season.